Securities Issuance Considerations As an External Funding Source for Sharia Commercial Banks - Ida Syafrida; Indianik Aminah; Taufik Awaludin (Economica: Jurnal Ekonomi Islam, 2020)
Abstract: This research is to formulate dominant aspects and sub-aspects of benefits, opportunities, costs, risks for the Issuance of Sukuk and shares as an external funding source for Sharia Banks (IBs). The fundamental problem is related to the less optimal role of Islamic banking in the national economy because the market share is 5.94% (early 2019). It is necessary to increase external funding sources through the Issuance of Sukuk and shares. There were 3 IBs share issuers: BPDS, BRIS, BTPNS, and 4 IBs Sukuk issuers: BMI, BSM, BNIS, BRIS. The method uses Analytic Network Process to identify dominant aspects and sub-aspects that IBs consider to issue Sukuk and shares. The primary data from in-depth interviews with each 5 Sukuk and share issuer expert practitioners of  IBs Treasury and Corporate Planning. The consideration of  IBs is much influenced by the benefit and opportunity aspects. Dominant sub-aspects of  IBs considerations in Sukuk issuance: sources of funds for capital and business expansion (benefit aspects), oversubscribed investor demand (opportunity aspects), cost of capital (cost aspects), sharia compliance risks (risk aspects). Dominant sub-aspects of public share issuance: increasing capital (benefit aspect), broad investor base (opportunity aspect), underwriter costs (cost aspect), information disclosure demands (risk aspect).Abstrak: Penelitian ini untuk merumuskan aspek dan sub-aspek dominan dari manfaat, peluang, biaya, dan risiko (BOCR) atas penerbitan sukuk dan saham publik sebagai sumber pendanaan eksternal Bank Umum Syariah (BUS). Dasar masalah terkait belum optimalnya peran perbankan syariah dalam perekonomian nasional karena pangsa pasar yang baru mencapai 5,94% dari total perbankan nasional (awal tahun 2019).  Ini disebabkan minimnya permodalan dan skala industri serta individual BUS, sehingga perlu peningkatan sumber pendanaan eksternal melalui penerbitan sukuk dan saham publik. Di awal 2019 terdapat 3 BUS emiten saham: BPDS, BRIS, BTPNS dan 4 BUS emiten sukuk: BMI, BSM, BNIS, BRIS. Metode analisis data menggunakan Analytic Network Process untuk mengidentifikasi aspek dan sub-aspek dominan yang menjadi pertimbangan BUS menerbitkan sukuk dan saham publik. Data utama hasil wawancara terhadap masing-masing 5 praktisi ahli Treassury dan Corporate Planning BUS emiten saham dan emiten sukuk. Pertimbangan BUS dominan dipengaruhi aspek manfaat kemudian aspek peluang.  Sub-aspek dominan pertimbangan BUS dalam penerbitan sukuk yaitu: sumber dana ekspansi usaha dan permodalan (aspek manfaat), permintaan investor berlebih (aspek peluang), biaya modal (aspek biaya), risiko kepatuhan syariah (aspek risiko). Sub-aspek dominan penerbitan saham publik yaitu: meningkatkan permodalan (aspek manfaat), luasnya basis investor (aspek peluang), biaya penjamin emisi (aspek biaya), tuntutan keterbukaan informasi (aspek risiko).